Enhanced Photostability of Lead Halide Perovskite Nanocrystals with Mn3+ Incorporation - Hu, Huiying; Fehn, Dominik; Barr, Maissa; Harreiß, Christina; Zhao, Yicheng; Meyer, Karsten; Osvet, Andres; Brabec, Christoph (ACS Applied Materials and Interfaces, 2024)
Recently, lead halide perovskite nanocrystals (NCs) have shown great potential and have been widely studied in lighting and optoelectronic fields. However, the long-term stability of perovskite NCs under irradiation is an important challenge for their application in practice. Mn2+ dopants are mostly proposed as substitutes for the Pb site in perovskite NCs synthesized through the hot-injection method, with the aim of improving both photo- and thermal stability. In this work, we employed a facile ligand-assisted reprecipitate strategy to introduce Mn ions into perovskite lattice, and the results showed that Mn3+ instead of Mn2+, even with a very low level of incorporation of 0.18 mol % as interstitial dopant, can enhance the photostability of perovskite binder film under the ambient conditions without emission change, and the photoluminescent efficiency can retain 70% and be stable under intensive irradiation for 12 h. Besides, Mn3+ incorporation could prolong the photoluminescent decay time by passivating trap defects and modifying the distortion of the lattice, which underscores the significant potential for application as light emitters.
CRIS-Team Scopus Importer:2024-05-17
Keywords: interstitial doping; passivation; perovskite nanocrystal; photoluminescence; photostability